Dulzura percibida de Aspartame y Sacarosa en Yogur - Hernandez Montes, A.=700 1 Palomo Lopez, E.; Santos Moreno, A.
(En, Es)
ilus., 7 ref.
Keywords: ASPARTAMO; EDULCORANTES ARTIFICIALES; SUCROSA; ANALISIS ORGANOLEPTICO; CONSISTENCIA; ACIDEZ; YOGUR; MEXICO; DULZURA